Com que atributos você me define? : um estudo sobre a imagem organizacional de uma instituição de ensino pública na perspectiva do público interno - Costa, Juciéli Alves da (2024)
This study aims to investigate the attributes that form the organizational image of Ifes, as perceived by the internal public of Ifes - Campus Serra, including students, faculty, and administrative staff. To support the research, the following topics were addressed: image management, identity, organizational image and reputation, as well as themes related to organizational communication, public communication, and internal public, relating how these topics influence the organizational image. Methodologically, the Image Configuration Method (ICM), proposed by Schuler and De Toni (2015), encompassing both qualitative and quantitative approaches, was applied. In the qualitative stage, data collection was carried out through structured interviews to identify the main attributes that form the organizational image of Ifes, from the perspective of students, faculty, and administrative staff. Data analysis in this phase was based on Bardin's content analysis (2016). The terms and variables extracted from this analysis were used to prepare the questionnaire for the next phase. In the quantitative phase, data collection was conducted through a questionnaire, which measured the degree of importance and satisfaction regarding the attributes identified in the previous stage. The results revealed that the organizational image of Ifes - Campus Serra is formed by 25 attributes, some of which are negative. The central image is composed of the attributes: Educational Excellence; Pleasant Environment; Pride; Developed Activities; Hostile Environment; Transformative Education; and Interpersonal Relationships. Regarding the dimensions of the image, it is influenced by rational and emotional attributes. In terms of importance, all attributes are considered very important by the three groups. In terms of satisfaction, students perceive reputation, pride, autonomy, professional and technical training, innovation, and technology as well-rated attributes. From the faculty's perspective, reputation, pride, and the activities carried out at the institution are well evaluated. For administrative staff, only the location is well evaluated